Anti-proliferation effects of ethanolic extracts from Sophora moorcroftiana seeds on human hepatocarcinoma HepG2 cell line. Issue 12 (18th June 2018) - Su, Gang; Yang, Wenke; Meng, Wenbo; Wu, Qionghui; Luo, Yanping; Ma, Xingming; Zhao, Shen; Xie, Xiaodong; Guo, Guang-Qin
Abstract: Previous studies have shown that the ethanolic extracts from Sophora moorcroftiana seeds (ee-Sms) have in vitro anticancer properties. The anti-proliferation effects of ee-Sms on HepG2 cells were assessed by MTT assay and cell cycle analysis. Total cell proteins were separated by two-dimensional electrophoresis (2-DE), and protein spots with more than two-fold difference were analysed by MALDI-TOF/TOF-MS. MTT assay showed that the anti-proliferation of ee-Sms demonstrates dose- and time dependently. HepG2 cells were treated with ee-Sms at 1.30 mg/mL for 48 h induced cell cycle arrest in S phase. The differentially-expressed proteins were involved in DNA repair, cell proliferation, cell metabolism and immunoreaction. This study sheds new insights into the molecular mechanisms underlying the anti-proliferation properties of ee-Sms in HepG2 cells. Abstract :